The Dependency of Kinetic Parameters as a Function of Initial Solute Concentration: New Insight from Adsorption of Dye and Heavy Metals onto Humic-Like Modified Adsorbents - Rahmat Basuki; Bambang Rusdiarso; Sri Juari Santosa; Dwi Siswanta (Bulletin of Chemical Reaction Engineering & Catalysis, 2021)
Kinetics parameters are the essential issue in the design of water treatment systems for pollutants uptake. Though numerous studies have identified the boundary conditions that exert influence on the kinetics parameters, the influence of the dynamic initial solute concentration (C0) to the kinetic parameters generated from fitting kinetics model to experimental data has not been investigated thoroughly. This study revealed a change in the kinetics parameter value due to changes in the adsorption mechanism as an effect of dynamic C0. It was observed that at higher C0 the adsorbed solute at equilibrium (qe) increases and it takes longer time to reach equilibrium. As a result, the kinetics rate constant (k) calculated from adsorption reaction model (Lagergren, Ho, Santosa, and RBS) was decreased. In general, Ho model exhibit higher correlation coefficient value (R2) among the other model at low C0. At high C0, Ho’s R2 tend to decrease while the Lagergren and RBS’s R2 was increased. The amendment mechanism from external mass transport to intra-particle diffusion as a rate limiting step was evidenced by Boyd and Weber-Morris kinetics model. Further, the physicochemical properties of the adsorbent used in this work: chitin and Fe3O4 modified horse dung humic acid (HDHA-Fe3O4 and HDHA-Ch, respectively) with the solute: Pb(II), Methylene Blue (MB), and Ni(II) was deeply discussed in this paper. The outcomes of this work are of prime significance for effective and optimum design for pollutant uptake by adsorption equipment. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).